Thirteen years of an international external quality assessment scheme for genotyping: results and recommendations - Haselmann, Verena; Eichner, Romy; Hetjens, Svetlana; Neumaier, Michael (Clinical chemistry, 2016)
Background: Suboptimal laboratory procedures resulting in genotyping errors, misdiagnosis, or incorrect reporting bear greatly on a patient's health management, therapeutic decisions made on their behalf, and ultimate outcome. Participation in external quality assessment (EQA) is a key element of quality assurance in molecular genetic diagnostics. Therefore, the Reference Institute for Bioanalytics has tried for 13 years to improve the quality of genetic testing by offering an EQA for different clinically relevant sequence variations. - Methods: Within each of the biannual EQA schemes offered, up to 18 samples of lyophilized human genomic DNA were provided for up to 50 different molecular genetic tests. Laboratories were asked to use their routine procedures for genotyping. At least 2 expert peer assessors reviewed the final returns. Data from 2002 to 2014 were evaluated. - Results: In total, 82 462 reported results from 812 characterized samples were evaluated. Globally, the number of participants increased each year along with the number of sequence variations offered. The error rate decreased significantly over the years with an overall error rate of 1.44%. Additionally, a decreased error rate for samples repeated over time was noted. Interestingly, the error rate showed a high difference depending on the locus analyzed and the method used. - Conclusions: Based on the evaluation of this long-term EQA scheme, various recommendations can be given to improve the quality of molecular genetic testing, such as the use of 2 different methods for genotyping. Furthermore, some methods are inappropriate for analysis of certain sequence variations.
Gesehen am 18.07.2019